Modified cyclic polyolefin material as well as preparation method and application thereof

By embedding norbornene and ethylene modified SBS in cyclic polyolefins, it improves its compatibility and performance, and solves the problem of insufficient dielectric loss and impact performance in high-frequency applications, and achieves higher frequency Possibility of application.

CN119286179AActive Publication Date: 2025-01-10WANHUA CHEM GRP CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411375047.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The application of cyclic polyolefins in the electronic and electrical fields is limited by the high dielectric loss requirements caused by the increase in frequency, and its impact performance is poor, making it difficult to meet the needs of future high-frequency applications.

Method used

Norbornene and ethylene are grafted into the styrene butadiene styrene elastic chain by chemical blocks and added to the cyclic polyolefin system to improve the compatibility and performance of the material, including antioxidants and lubricant addition to enhance thermal deformation and impact performance of the material while maintaining low dielectric loss.

Benefits of technology

It significantly improves the thermal deformation temperature and impact performance of cyclic polyolefins, and maintains the dielectric loss of no more than 0.0006 at low and high frequencies, broadening its application areas, especially suitable for higher frequencies 6G antenna base stations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068469480000021
    Figure BDA0005068469480000021
  • Figure BDA0005068469480000022
    Figure BDA0005068469480000022
  • Figure BDA0005068469480000081
    Figure BDA0005068469480000081
Patent Text Reader

Abstract

The invention provides a modified cyclic polyolefin material as well as a preparation method and application thereof. Norbornene and ethylene are grafted into a styrene-butadiene-styrene elastic chain in a chemical block manner, and then are added into a cyclic polyolefin system, so that the compatibility with an elastomer can be increased, and the impact resistance and the thermal deformation performance are greatly improved. Meanwhile, the low dielectric loss is kept at low frequency and high frequency and does not exceed 0.0006, the application field of cyclic polyolefin is widened, and the preparation method is simple in step and convenient for industrial implementation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a modified cyclic polyolefin material and a preparation method and application thereof. Background Art

[0002] As a new type of thermoplastic resin, cyclic polyolefin is a high-end optical material obtained by copolymerization of cyclic olefin and ethylene. Due to its excellent properties, such as high heat deformation temperature, high transparency, low birefringence, low dielectric loss, low dielectric constant, low water vapor permeability and good melt fluidity, it is widely used in various fields. Its high transparency can be used as a mobile phone optical lens, while its low dielectric constant and low dielectric loss can be used in electronic materials, such as chip packaging boxes and 5G antenna base station boxes. As the frequency increases, the requirements for low dielectric loss are getting higher and higher. At high frequencies, higher heat deformation performance and higher impact performance are required. The pure material has a strong rigidity and poor impact performance due to its annular structure. Therefore, in order to be better applied in this field in the future, it needs to be modified.

[0003] Chinese patent CN 108912578A discloses a modified cyclic polyolefin material and its application. In the invention, the heat deformation temperature is increased by using fibers with a dielectric constant of less than or equal to 8. However, the addition of fillers can often damage the compatibility of the cyclic polyolefin material, resulting in mechanical defects and reduced mechanical properties.

[0004] In summary, as the frequency of antenna base stations becomes higher and higher, the requirements for ultra-low dielectric loss of their internal materials are also getting higher and higher. The expansion of the application of cyclic polyolefins in electronic and electrical appliances requires improving their impact resistance and heat resistance. Summary of the invention

[0005] The object of the present invention is to provide a modified cyclic polyolefin, which can increase the compatibility with the elastomer by grafting norbornene and ethylene to the styrene butadiene styrene elastic chain by chemical blocking, and then add it to the cyclic polyolefin system, so as to significantly improve the impact resistance and thermal deformation performance. At the same time, the dielectric loss is kept low at low frequency and high frequency, not exceeding 0.0006, which broadens the application field of cyclic polyolefin. The preparation method of the present invention has simple steps and is easy to realize industrialization.

[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0007] In a first aspect, the present invention provides a modified cyclic polyolefin material, comprising the following components in parts by weight:

[0008] Cyclic polyolefin resin 100 parts

[0009] 1-30 parts of elastomer, for example 5, 10, 15, 20, 25, 30 parts;

[0010] Other additives 0-1 part, for example 0.2, 0.5, 0.8, 1 part.

[0011] In the present invention, the cyclic polyolefin resin is an injection molding grade COC material, and the melt flow rate of the resin under the conditions of 260° C. and 2.16 kg is greater than or equal to 4 g / 10 min, preferably 4-15 g / 10 min.

[0012] In the present invention, the elastomer is norbornene and ethylene modified SBS;

[0013] Specifically, the elastomer has the following structure:

[0014]

[0015] Wherein, the R1 is the following structure:

[0016]

[0017] Among them, m:y:(x+z) is (5-10):(60-75):(20-30), p:q is (10-30):

[0018] (90-70).

[0019] In the present invention, the other additives include antioxidants, lubricants, etc., which can be added by those skilled in the art as needed;

[0020] Specifically, the antioxidant may be selected from one or more of 1076, 168, 1010, 618, and 686;

[0021] Specifically, the lubricant can be selected from ethylene bisstearamide and the like.

[0022] In a second aspect, the present invention provides a method for preparing the above-mentioned elastomer.

[0023] The preparation method of the elastomer comprises the following steps:

[0024] In an inert atmosphere, styrene and an initiator are mixed with a non-polar hydrocarbon solvent system to carry out a first-stage polymerization reaction. After the first-stage polymerization reaction is completed, a structure regulator and butadiene are added to the system to carry out a second-stage polymerization reaction. After the second-stage polymerization reaction is completed, norbornene and ethylene are added to the system, and a catalyst is added to carry out a third-stage polymerization reaction to obtain norbornene and ethylene modified SBS.

[0025] In the present invention, the initiator is an organic lithium initiator, preferably n-butyl lithium or sec-butyl lithium.

[0026] In the present invention, the amount of initiator used in the polymerization process depends on the designed size of the molecular weight. Generally, the amount of initiator used can be 0.5-2 mmol, preferably 0.8-1.4 mmol, per 100 g of the total amount of styrene and butadiene.

[0027] In the present invention, the non-polar hydrocarbon solvent is selected from cyclohexane and / or hexane, preferably cyclohexane.

[0028] In the present invention, the non-polar hydrocarbon solvent is such that the total concentration of styrene and butadiene is 10wt%-25wt%.

[0029] In the present invention, the temperature of the first stage polymerization reaction is 50-60° C., and the polymerization reaction time is 20-25 min.

[0030] In the present invention, the structure regulator is at least one of tetrahydrofurfuryl alcohol ethyl ether, ditetrahydrofurfuryl propane, tetrahydrofurfuryl amine, and tetrahydrofurfuryl alcohol hexyl ether, preferably tetrahydrofurfuryl alcohol ethyl ether.

[0031] In the present invention, the molar ratio of the structure regulator to the initiator is 0.01-0.05:1.

[0032] In the present invention, during the two-stage polymerization process, the initial polymerization temperature is 65-70°C, and the temperature is increased at a heating rate of 0.5-1°C / min, the polymerization temperature is controlled to be no higher than 80°C, and the reaction time is 20-25min;

[0033] In the present invention, the catalyst is methylaluminoxane.

[0034] In the present invention, the amount of the catalyst is 0.1 mmol to 1 mmol, preferably 0.5 to 0.8 mmol, per 100 g of the total amount of norbornene and ethylene.

[0035] In the present invention, the temperature of the three-stage polymerization reaction is 80-100° C., and the reaction time is 30 min-35 min.

[0036] In the present invention, the polymerization pressure in the first, second and third stages is maintained at 0.2-0.3 MPa.

[0037] In a third aspect, the present invention provides a method for preparing a modified cyclic polyolefin material, comprising the following steps: adding a cyclic polyolefin resin, an elastomer, and optional other additives such as an antioxidant and a lubricant to a high-speed mixer for thorough mixing, adding the mixture to a twin-screw extruder for extrusion granulation, and preparing the cyclic polyolefin material.

[0038] Specifically, the preparation method is to add the raw materials together into a high-speed mixer, mix them thoroughly, and then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36-40 through a feeder, and the extrusion temperature is 200-260°C.

[0039] The cyclic polyolefin material of the present invention has a heat deformation temperature of not less than 135° C., an impact strength of greater than 150 J / m, and a dielectric loss of not more than 0.0006 at low frequency and high frequency.

[0040] Fourthly, the modified cyclic polyolefin material of the present invention can be applied to communications, radar, aerospace, smart wearables, imaging, global positioning and other fields.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] By chemically grafting the norbornene groups into the styrene butadiene styrene elastomer, the compatibility with the cyclic polyolefin matrix is ​​increased, giving the material higher impact performance. At the same time, the elastomer also increases the thermal deformation temperature of the material, maintaining the original low dielectric loss of the material under low and high frequency conditions, allowing the material to be widely used in future higher frequency 6G antenna base stations. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below, but the implementation manner of the present invention is not limited thereto.

[0044] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0045] The raw materials used in the following examples and comparative examples are as follows:

[0046] Cyclic polyolefin resin: brand 6015, melt flow rate at 260°C, 2.16Kg load conditions of 4g / 10min, Japan Polyplastics Co., Ltd.; brand 6013, melt flow rate at 260°C, 2.16Kg load conditions of 13g / 10min, Japan Polyplastics Co., Ltd.

[0047] Styrene: 99%, J&K Technologies;

[0048] Butadiene: 99%, containing inhibitor, J&K Technology;

[0049] Ethylene: 99%, J&K Technology;

[0050] Norbornene: 98%, TCI;

[0051] Tetrahydrofurfuryl alcohol ethyl ether: 99%, TCI;

[0052] n-Butyl lithium: 0.5 mol / L hexane solution, J&K Technology;

[0053] Cyclohexane: 99%, J&K Technologies;

[0054] Methylaluminoxane: toluene solvent, concentration 10wt%, Albemarle Corporation, USA;

[0055] Lubricant: EBS, Jinan Quanxing New Materials Co., Ltd.;

[0056] Antioxidants: 168 and 1076, Tianjin Lianlong Co., Ltd.

[0057] The conventional mechanical properties, thermal properties and electrical properties of modified cyclic polyolefin materials are tested according to the following standards:

[0058] Izod notched impact strength: tested according to ASTM D256 standard, impact energy is 2.75J;

[0059] Melt flow rate (MFR): tested according to ASTM D1238 standard, test conditions: 260℃ / 2.16kg;

[0060] Heat deformation temperature (HDT): according to ISO 75, 0.45MPa;

[0061] Dielectric constant: IEC 60250, test conditions 1GHZ, 15GHZ;

[0062] Dielectric loss: IEC 60250, test conditions 1GHZ, 15GHZ.

[0063] Preliminary Example 1

[0064] In a 5-liter steel polymerization kettle under nitrogen protection, 2800 mL of cyclohexane was added, and then 208 g of styrene was injected into the polymerization kettle at the same time. After the temperature rose to 55°C, 9.8 mL of 0.5 mol / L n-butyl lithium was injected into the polymerization kettle with a syringe to carry out the first stage initiation polymerization. The polymerization pressure was 0.25 MPa. After reacting for 20 minutes, the second stage starting temperature was controlled at 65°C, and then 405 g of butadiene and 0.019 g of tetrahydrofurfuryl alcohol ethyl ether were uniformly pressed into the polymerization kettle with nitrogen. The temperature rise rate was controlled at 1°C / min. After the second stage polymerization temperature reached the maximum temperature of 75°C, the reaction was continued for 20 minutes. 47 g of norbornene and 126 g of ethylene were continued to be added to the kettle, and 0.15 g of methylaluminoxane was introduced. The reaction temperature was 90°C, the reaction time was 30 minutes, and the product after drying at 90°C was recorded as A.

[0065] Preliminary Example 2

[0066] In a 5-liter steel polymerization kettle under nitrogen protection, 2800 mL of cyclohexane was added, and then 208 g of styrene was injected into the polymerization kettle at the same time. After the temperature rose to 55°C, 12.26 mL of 0.5 mol / L n-butyl lithium was injected into the polymerization kettle with a syringe to carry out the first stage initiation polymerization. The polymerization pressure was 0.25 MPa. After reacting for 25 minutes, the second stage starting temperature was controlled at 65°C, and then 405 g of butadiene and 0.039 g of tetrahydrofurfuryl alcohol ethyl ether were uniformly pressed into the polymerization kettle with nitrogen. The temperature rise rate was controlled at 1°C / min. After the second stage polymerization temperature reached the maximum temperature of 75°C, the reaction was continued for 20 minutes. 94 g of norbornene and 112 g of ethylene were continued to be added to the kettle, and 0.29 g of methylaluminoxane was introduced. The reaction temperature was 100°C, the reaction time was 30 minutes, and the product was recorded as B after drying at 90°C.

[0067] Preparatory Example 3

[0068] In a 5-liter steel polymerization kettle under nitrogen protection, 2800 mL of cyclohexane was added, and then 260 g of styrene was injected into the polymerization kettle at the same time. After the temperature rose to 55°C, 12.22 mL of 0.5 mol / L n-butyl lithium was injected into the polymerization kettle with a syringe to carry out the first stage initiation polymerization. The polymerization pressure was 0.25 MPa. After the reaction for 20 minutes, when the second stage starting temperature was controlled at 65°C, 351 g of butadiene and 0.039 g of tetrahydrofurfuryl alcohol ethyl ether were uniformly pressed into the polymerization kettle with nitrogen. If necessary, cooling water was introduced to control the temperature rise rate, that is, the temperature rise rate was controlled at 1°C / min. After the second stage polymerization temperature reached the maximum temperature of 75°C, the reaction was continued for 20 minutes. 188 g of norbornene and 224 g of ethylene were continued to be added to the kettle, and 0.57 g of methylaluminoxane was introduced. The reaction temperature was 100°C, the reaction time was 30 minutes, and the product after drying at 90°C was recorded as C.

[0069] Preliminary Example 4

[0070] In a 5-liter steel polymerization kettle under nitrogen protection, 2800 mL of cyclohexane was added, and then 260 g of styrene was injected into the polymerization kettle at the same time. After the temperature rose to 55°C, 12.22 mL of 0.5 mol / L n-butyl lithium was injected into the polymerization kettle with a syringe to carry out the first stage initiation polymerization. The polymerization pressure was 0.25 MPa. After reacting for 25 minutes, the second stage starting temperature was controlled at 65°C, and then 351 g of butadiene and 0.039 g of tetrahydrofurfuryl alcohol ethyl ether were uniformly pressed into the polymerization kettle with nitrogen. The temperature rise rate was controlled at 1°C / min. After the second stage polymerization temperature reached the maximum temperature of 75°C, the reaction was continued for 20 minutes. 282 g of norbornene and 196 g of ethylene were continued to be added to the kettle, and 0.66 g of methylaluminoxane was introduced. The reaction temperature was 100°C, the reaction time was 30 minutes, and the product after drying at 90°C was recorded as D.

[0071] Preliminary Example 5

[0072] In a 5-liter steel polymerization kettle under nitrogen protection, 2800 mL of cyclohexane was added, and then 260 g of styrene was injected into the polymerization kettle at the same time. After the temperature rose to 55°C, 13.3 mL of 0.5 mol / L n-butyl lithium was injected into the polymerization kettle with a syringe to carry out the first stage initiation polymerization. The polymerization pressure was 0.25 MPa. After reacting for 25 minutes, the second stage starting temperature was controlled at 65°C, and then 405 g of butadiene and 0.043 g of tetrahydrofurfuryl alcohol ethyl ether were uniformly pressed into the polymerization kettle with nitrogen. The temperature rise rate was controlled at 1°C / min. After the second stage polymerization temperature reached the maximum temperature of 75°C, the reaction was continued for 20 minutes. The product was recorded as E after drying at 90°C.

[0073] Example 1

[0074] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0075] 100 parts of 6015 resin, 20 parts of A, 0.1 part of 1076, 0.2 part of 168, 0.3 part of EBS.

[0076] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0077] Example 2

[0078] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0079] 100 parts of 6013 resin, 20 parts of B, 0.1 part of 1076, 0.2 part of 168, 0.3 part of EBS.

[0080] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0081] Example 3

[0082] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0083] 100 parts of 6015 resin, 20 parts of C, 0.1 part of 1076, 0.2 parts of 168, and 0.3 parts of EBS.

[0084] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0085] Example 4

[0086] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0087] 100 parts of 6015 resin, 10 parts of D, 0.1 parts of 1076, 0.2 parts of 168, and 0.3 parts of EBS.

[0088] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0089] Example 5

[0090] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0091] 100 parts of 6015 resin, 20 parts of D, 0.1 part of 1076, 0.2 parts of 168, and 0.3 parts of EBS.

[0092] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0093] Example 6

[0094] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0095] 100 parts of 6015 resin, 30 parts of D, 0.1 part of 1076, 0.2 parts of 168, and 0.3 parts of EBS.

[0096] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0097] Comparative Example 1

[0098] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0099] 100 parts of 6015 resin, 0.1 part of 1076, 0.2 part of 168, 0.3 part of EBS.

[0100] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0101] Comparative Example 2

[0102] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0103] 100 parts of 6015 resin, 10 parts of E, 0.1 part of 1076, 0.2 part of 168, and 0.3 part of EBS.

[0104] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0105] Comparative Example 3

[0106] The special raw material is obtained according to the following ratio (weight percentage) and preparation method:

[0107] 100 parts of 6015 resin, 20 parts of norbornene, 0.1 parts of 1076, 0.2 parts of 168, and 0.3 parts of EBS.

[0108] Add them into a high-speed mixer in the above proportion and mix thoroughly for 10 minutes. Then add the materials into a twin-screw extruder with a length-to-diameter ratio of 36 through a feeder. The extrusion temperatures are 200°C, 240°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, to obtain modified cyclic polyolefin materials.

[0109] The samples were injection molded into general processing technology specimens for testing. The following are the performance test data of each embodiment and comparative example:

[0110]

[0111]

[0112] Through testing, it was found that after adding the newly synthesized elastomer, the modified cyclic polyolefin can have a higher heat deformation temperature and can cope with the high heat environment brought by high-frequency base stations. At the same time, the impact strength of the modified material is greatly improved, and it maintains very excellent dielectric loss at high and ultra-high frequencies, broadening its future use for higher frequency base stations.

Claims

1. A modified cyclic polyolefin material, characterized in that: By weight, it includes the following components: 100 parts of cyclic polyolefin resin, 1-30 parts of elastomer; The elastic body has the following structure: The R1 is the following structure, Among them, m:y:(x+z) is (5-10):(60-75):(20-30), p:q is (10-30): (90-70)。 2. The modified cyclic polyolefin material according to claim 1, characterized in that: The cyclic polyolefin resin is an injection molding grade COC material, and preferably has a melt flow rate greater than or equal to 4 g / 10 min, preferably 4-15 g / 10 min, under the conditions of 260° C. and 2.16 kg.

3. The modified cyclic polyolefin material according to claim 1, characterized in that: The modified cyclic polyolefin material also includes other additives, which are selected from antioxidants and lubricants; the antioxidant is preferably one or more of 1076, 168, 1010, 618, and 686; the lubricant is preferably ethylene bisstearamide.

4. A method for preparing an elastomer in a modified cyclic polyolefin material as claimed in any one of claims 1 to 3, characterized in that: The following steps are included: (1) mixing styrene and an initiator with a non-polar hydrocarbon solvent to carry out a polymerization reaction; (2) After the first stage polymerization reaction is completed, a structure regulator and butadiene are added to the system to carry out a second stage polymerization reaction; (3) After the second stage polymerization reaction is completed, norbornene, ethylene and a catalyst are added to the system to carry out a third stage polymerization reaction.

5. The method according to claim 4, characterized in that: The initiator in step (1) is n-butyl lithium or sec-butyl lithium; preferably, the non-polar hydrocarbon solvent is cyclohexane and / or hexane, more preferably cyclohexane.

6. The method according to claim 4, characterized in that The temperature of the first stage polymerization reaction in step (1) is 50-60°C, and the polymerization reaction time is 20-25min; preferably, during the second stage polymerization process in step (2), the initial polymerization reaction temperature is 65-70°C, and the temperature is increased at a rate of 0.5-1°C / min, the polymerization reaction temperature is controlled to be no more than 80°C, and the reaction time is 20-25min.

7. The method according to claim 4, characterized in that: The structure regulator in step (2) is at least one of tetrahydrofurfuryl alcohol ethyl ether, ditetrahydrofurfuryl propane, tetrahydrofurfuryl amine, and tetrahydrofurfuryl alcohol hexyl ether, preferably tetrahydrofurfuryl alcohol ethyl ether; preferably, the molar ratio of the structure regulator to the initiator is 0.01-0.05:

1.

8. The method according to claim 3, characterized in that: The catalyst in step (3) is methylaluminoxane, and the amount of the catalyst is 0.1mmol-1mmol, preferably 0.5-0.8mmol, per 100g of the total amount of norbornene and ethylene; preferably, the pressure of the first, second and third stage polymerization reactions is maintained at 0.2-0.3MPa.

9. A method for preparing the modified cyclic polyolefin material according to claim 1 or 2, characterized in that: The components are mixed and added into the main feeding system of the extruder, and mixed, extruded and granulated by the extruder to obtain the modified cyclic polyolefin material.

10. Application of the modified cyclic polyolefin material according to claim 1 or 2 or the modified cyclic polyolefin material prepared by the preparation method according to claim 9 in the fields of communication, radar, aerospace, smart wearables, imaging, and global positioning.

Citation Information

Patent Citations

  • Modified cyclic polyolefin material and application thereof

    CN108912578A

  • Thermoplastic elastomer (TPE) taking consideration to both low dielectric constant and fire resistance and preparation method thereof

    CN110283386A

  • High-transparency low-dielectric-loss toughened cyclic polyolefin material and preparation method thereof

    CN112457617A

  • Hydrogenated styrene thermoplastic elastomer and preparation method thereof

    CN113956412A

  • High-modulus high-toughness cycloolefin copolymer material and preparation method thereof

    CN114806060A